Solid state chemistry : - Smart, Lesley E. (CRC Press, 2005)
Solid state and materials chemistry is a rapidly evolving field. Smart and Moore, who both teach inorganic chemistry at the Open U., UK, have added a new chapter on the solid state aspects of nanoscience. The text also expands coverage of techniques used to characterize solids and includes updated sections on such hot topics as fuel cells, organic polymers, organic superconductors, fullerenes, photonics, and giant and colossal magnetoresistance. The well-illustrated text includes review questions and the prefaces of the earlier (undated) editions.